Attitudes of psychotherapists towards their own performance and the role of the social comparison group: The self-assessment bias in psychodynamic, humanistic, systemic, and behavioral therapists - Probst, Thomas; Humer, Elke; Jesser, Andrea; Pieh, Christoph (Frontiers in Psychology, 2022)
Studies report that psychotherapists overestimate their own performance (self-assessment bias). This study aimed to examine if the self-assessment bias in psychotherapists differs between therapeutic orientations and/or between social comparison groups. Psychotherapists gave subjective estimations of their professional performance (0–100 scale from poorest to best performance) compared to two social comparison groups (“all psychotherapists” vs. “psychotherapists with the same therapeutic approach”). They further rated the proportion of their patients recovering, improving, not changing, or deteriorating. In total, N = 229 Austrian psychotherapists (n = 39 psychodynamic, n = 121 humanistic, n = 48 systemic, n = 21 behavioral) participated in the online survey. Psychotherapists rated their own performance on average at M = 79.11 relative to “all psychotherapists” vs. at M = 77.76 relative to “psychotherapists with the same therapeutic approach” (p < 0.05). This was not significantly different between therapeutic orientations. A significant interaction between social comparison group and therapeutic orientation (p < 0.05) revealed a drop of self-assessement bias in social comparison group “same approach” vs. “all psychotherapists” in psychodynamic and humanistic therapists (p < 0.05). Psychotherapists overestimated the proportion of patients recovering (M = 44.76%), improving (M = 43.73%) and underestimated the proportion of patients not changing (M = 9.86%) and deteriorating (M = 1.64%), with no differences between orientations. The self-assessment bias did not differ between therapeutic orientations, but the social comparison group appears to be an important variable. A major drawback is that results have not been connected to patient-reported outcome or objectively rated performance parameters.